Expansion through Sea: China’s Maritime Story - Reyes, Joan Tara (Hukay; Vol 19 (2014))
China as a Sea Power, 1127-1368: A Preliminary Survey of the Maritime Expansion and Naval Exploits of the Chinese People during the Southern Song and Yuan Periods Written by Lo Jung-pan Edited by Bruce A. Elleman. (1957)2011. Singapore: NUS Press and Hong Kong University Press